2013
DOI: 10.1074/jbc.m112.430892
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation by the m-AAA Protease Increases the Threshold Hydrophobicity for Retention of Transmembrane Helices in the Inner Membrane of Yeast Mitochondria

Abstract: Background:The m-AAA protease dislocates transmembrane segments from the mitochondrial inner membrane. Results:The presence of the m-AAA protease increases the hydrophobicity required for a transmembrane segment to remain in the membrane. Conclusion: The hydrophobicity thresholds for transmembrane segment retention in the mitochondrial inner membrane differ with or without the m-AAA protease. Significance: Retention of a transmembrane domain in the inner membrane depends on recognition by the m-AAA protease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Recently, the conformational stability has been shown to be a key determinant for the cellular trafficking efficiency of the human membrane protein PMP22 65 . In yeast, the presence of a mitochondrial FtsH ortholog increases the threshold hydrophobicity level of a TM helix for its retention in the inner membrane 66 . Our systematic study dissecting the effects of the two physical forces further supports these observations.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the conformational stability has been shown to be a key determinant for the cellular trafficking efficiency of the human membrane protein PMP22 65 . In yeast, the presence of a mitochondrial FtsH ortholog increases the threshold hydrophobicity level of a TM helix for its retention in the inner membrane 66 . Our systematic study dissecting the effects of the two physical forces further supports these observations.…”
Section: Discussionmentioning
confidence: 99%
“…This draws the substrate proteins inside the pore and unfolds them (Lee et al, 2001;Langklotz et al, 2012). In yeast mitochondria, the m-AAA protease, described as an ATP-dependent protease that degrades misfolded proteins and mediates protein processing, is proposed to be further involved in the dislocation of imported preproteins from the inner membrane by functioning as an ATP-driven molecular motor (Tatsuta et al, 2007;Botelho et al, 2013). In yeast mitochondria, many nucleus-encoded preproteins are imported into the mitochondrial matrix via the TIM23 translocon (Demishtein-Zohary and Azem, 2017).…”
Section: Possible Role Of the Ftsh12-ftshi Complexmentioning
confidence: 99%
“…A study examining the retention of simple transmembrane sequences in the MIM demonstrated that sequences required >3:1 leucine:alanine residues to escape dislocation from the membrane by m-AAA. Under this scheme, the protease could extract most MIM proteins (Botelho et al, 2013 ). The central pores of both proteases contain loops bearing the canonical aromatic-hydrophobic (Ar-ϕ) motif that are proposed to deliver the translocating force (Graef and Langer, 2006 ; Martin et al, 2008 ).…”
Section: Mechanisms Of Extraction From the Membranementioning
confidence: 99%